Direito regulatório na responsabilidade social das empresas: a promoção do desenvolvimento sustentável pela via da doutrina humanista - Vergani, Andréa de Melo (2011)
Scientific progress and new information technologies led to the society s model in the XXI century. Mankind gradually becomes aware that the development should take place through mechanisms that reconcile the economic, social and environmental impacts, ensuring the sustainability of the planet and the consequent survival of future generations. In this context, Corporate Social Responsibility emerges as an ideal model of progress, because it proposes the harmony of the tripod economy/society/environment, sponsoring human dignity as a fundamental element for development. It is, therefore, based on bibliographical survey that the present research intends to identify the instruments for enabling sustainable development, as well the legal instruments that guide its accomplishment. At the end, in a propositive way will be pointed guiding paradigms of human action for achieving progress without compromising the planet's life